2019
DOI: 10.3892/ijo.2019.4691
|View full text |Cite
|
Sign up to set email alerts
|

Muscleblind‑like 1 destabilizes Snail mRNA and suppresses the metastasis of colorectal cancer cells via the Snail/E‑cadherin axis

Abstract: RNA-binding proteins (RBPs) play a fundamental role in the recurrence and metastasis of colorectal cancer (CRC). In this study, we identified muscleblind-like 1 (MBNL1), an RBP implicated in developmental control, as a robust suppressor of CRC cell metastasis in vitro. By using a scratch assay coupled with time-lapse live cell imaging, our findings revealed that the knockdown of MBNL1 induced epithelial-to-mesenchymal transition (EMT)-like morphological changes in the HCT-116 cells, accompanied by an enhanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 39 publications
(41 reference statements)
3
21
0
Order By: Relevance
“…It has been shown that MBNL1 suppresses breast cancer metastatic colonization through regulating transcript stabilization 18 . A recent study showed that MBNL1 inhibited colorectal cancer metastasis by modulation of the Snail/E-cadherin axis 19 . Furthermore, another family member MBNL3, was found to act as an oncogene, because it promoted tumorigenesis and its high expression indicated poor prognosis in hepatocellular carcinoma 20 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that MBNL1 suppresses breast cancer metastatic colonization through regulating transcript stabilization 18 . A recent study showed that MBNL1 inhibited colorectal cancer metastasis by modulation of the Snail/E-cadherin axis 19 . Furthermore, another family member MBNL3, was found to act as an oncogene, because it promoted tumorigenesis and its high expression indicated poor prognosis in hepatocellular carcinoma 20 .…”
Section: Introductionmentioning
confidence: 99%
“…MBNL1 was demonstrated to be a master splicing regulator for shaping transcriptomic profiles throughout the development of striated muscle and blood lineages [42 , 43] . Even though the tumor-suppressive influence of MBNL1 toward cancer cells via AS regulation was recently revealed [23] , the MBNL1 isoform was reported to exert an opposite effect on carcinogenic signatures [24] . The presence of the MBNL1 isoform lacking exon 7 was shown to cause DNA damage, which in turn interfered with cell viability and migration [24] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the molecular mechanism involved in regulating MBNL1 and MBNL1-mediated impacts on tissue development, its influence on carcinogenesis was recently investigated. MBNL1 exerted potential effect on suppressing the progression of breast cancer and CRC possibly through AS regulation [22] , [23] , [24] .…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer is one of the most common malignant tumors of the digestive system, with more than 1.8 million newly diagnosed cases and 800,000 cancer related deaths around the world in 2018 [1]. In addition to tumorigenesis, tumor metastasis seems to be another important cause of cancer related death in patients with CRC [30]. Despite the treatment of cancer has made great progress in recent years, the underlying molecular mechanisms of tumorigenesis and metastasis are complex and worthy of further study.…”
Section: Discussionmentioning
confidence: 99%